Sistem Informasi Wisata Kuliner di Kota Medan Berbasis Web - Kartini, Erta; Silitonga, Parasian (MEANS (Media Informasi Analisa dan Sistem), 2018)
The advancement of information technology today is fueling the growth in the number of internet users. In the business world, the role of technology is very important, and it can be said that it has become a primary need for entrepreneurs in this period. Likewise about culinary that has used the internet network to present a variety of good information from information on place, taste, presentation and price in the field of information technology. But for culinary information in the city of Medan on a website, while it is still incomplete and there is no website that specializes in culinary tourism in Medan and its reservations. Therefore, it is necessary to design a web-based culinary tourism information system in Medan City to make it easier for people to find culinary varieties in the city of Medan.